PENGARUH STRUKTUR GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA SEKTOR TRANSPORTASI & LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Eko Reynaldi Saruksuk; Dina Arfianti Siregar; Ilham Hidayah Napitupulu; Deliana Deliana; Putri Syuhada (Jurnal Akuntansi dan Bisnis, 2026)
The goal of this research is to ascertain how the company's financial performance, as determined by Return On Asset (ROA), is impacted by an effective corporate governance structure that includes the board of directors, independent board of commissioners, audit committee, and institutional ownership. The purposive sampling approach, which involves selecting samples for transportation and logistics businesses listed on the Indonesia Stock Exchange for the 2019–2023 period based on specific criteria, is employed in this research. Twenty-three businesses make up the study's sample data. Multiple linear regression analysis is the analysis model that is employed. The results of this study show that the board of directors and the independent board of commissioners have a positive and significant effect on the company's financial performance. In contrast, the audit committee and institutional ownership have no significant effect on the company's financial performance. These findings indicate that strengthening the roles of the board of directors and independent commissioners can enhance corporate financial outcomes, while the audit committee and institutional ownership mechanisms may require further evaluation to become more effective in the transportation and logistics sector in Indonesia.